1989
DOI: 10.1111/j.1365-2621.1989.tb04650.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of Restructured Turkey Meat with Variable Alginate/Calcium‐Lactate Ratios

Abstract: Restructured ground turkey and turkey breast meat patties, formulated with combinations of O-1.0% sodium alginate, O-0.1875% calcium carbonate and 0.3.6% lactate, were compared to a no additive control. The ratio of sodium alginate to calcium carbonate was held constant at 5.3 to 1. Optimal sensory and instrumental raw and cooked product bind was achieved with combinations of 0.4-1.0% sodium alginatc, 0.0750-0.1875% calcium carbonate and 0.6% lactate. All reitructured products with the algin/calcium binder had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 8 publications
2
16
0
Order By: Relevance
“…Those restructured with salt/phosphate or Naalginate/Ca-lactate also had similar (P>O.O5) juiciness, except for steaks prepared with added water, which were juicier than controls. This agreed with Ensor et al (1989) who reported that addition of Na-alginate/Ca-lactate binder with no added water did not change (P>O.O5) juiciness of restructured turkey meat as determined by panelists. All mechanical treatments had no (P>O.O5) effect on cooked product juiciness.…”
Section: Sensory Evaluationsupporting
confidence: 93%
“…Those restructured with salt/phosphate or Naalginate/Ca-lactate also had similar (P>O.O5) juiciness, except for steaks prepared with added water, which were juicier than controls. This agreed with Ensor et al (1989) who reported that addition of Na-alginate/Ca-lactate binder with no added water did not change (P>O.O5) juiciness of restructured turkey meat as determined by panelists. All mechanical treatments had no (P>O.O5) effect on cooked product juiciness.…”
Section: Sensory Evaluationsupporting
confidence: 93%
“…Other hydrocolloids were also tested as binding agents. Ensor et al (1989) reported that an alginate and calcium binder increased cook yield of restructured turkey products.…”
Section: Introductionmentioning
confidence: 98%
“…Means and Schmidt (1986) indicated the ideal alginate:calcium ratio was 2.5 g alginate:0.18 g calcium ion. Ensor, Ernst, Sofos, and Schmidt (1986) made acceptable structured turkey meat using 0.4-1.0% sodium alginate, 0.075-0.1875% calcium carbonate, and 0.6% lactate. Later, Ensor, Sofos, and Schmidt (1990) found 0.4% sodium alginate, 0.075% calcium carbonate, and 0.6% lactate were optimal for use in structured meat products.…”
Section: Functional Characteristics and Propertiesmentioning
confidence: 99%